DESIGN AND EFFECTIVENESS OF SEQUENTIAL NUMBERING SYSTEMS IN THE REVENUE CYCLE: THEIR IMPACT ON AUDIT TRAIL, FRAUD DETECTION, AND MATERIAL MISSTATEMENT RISK - Tulus Pujo Nugroho (International Journal Management and Economic, 2025)
This study investigates the effectiveness of implementing a sequential numbering system within the revenue cycle and its impact on audit trail quality, fraud detection, and material misstatement risk in small and medium-sized enterprises (SMEs) in Indonesia. The research applies a quantitative explanatory approach using a survey of 120 respondents, supported by document verification on a subsample of 30 firms. Four main constructs were analyzed: Discipline of Sequential Numbering (DSN), Audit Trail Strength (ATS), Fraud Detection Capability (FDC), and Material Misstatement Risk Proxy (MMRP). The results of the Partial Least Squares–Structural Equation Modeling (PLS-SEM) show that DSN has a significant positive effect on ATS (β = 0.41; p < 0.01) and FDC (β = 0.36; p < 0.05), and a significant negative effect on MMRP (β = −0.28; p < 0.05). These findings indicate that disciplined sequential numbering strengthens the reliability and traceability of accounting records, enhances the ability to identify anomalies, and reduces the likelihood of material misstatement in financial statements. The study provides practical implications for internal control improvement, especially for SMEs adopting digital or semi-digital documentation systems. It also proposes a Sequential Numbering Discipline Index (SNDI) that can be adopted as a simple, low-cost metric to enhance internal control over financial reporting (ICFR).